(untitled) (Scientific journal of the Fergana State University, 2023)
During the years of independence, it was important to create various forms of ownership and their effective application in the process of implementing reforms in the socio-economic sphere, in providing the population with consumer goods, stabilizing and developing social relations, in connection with which cooperative enterprises are becoming increasingly important.In the changes carried out in this direction, in particular, the solution of such issues as the creation of the institution of a cooperative association of independent and interconnected enterprises, farms, dekhkan farms and owners of household plots into agricultural associations, as well as the development of cooperation between producers, historical experience plays an important role.Research from a new methodological position on the activities of production cooperatives in the postwar years, their role and place in the socio-economic life of the region is also of great importance in terms of solving the tasks setThe Soviet government instructed the cooperatives to expand cooperative trade along with the production of consumer goods.In this article, the role of production cooperatives operating in the economic development of the region since the Second World War in Fergana region, their role in the production of a wide range of consumer goods and their peculiarities were discussed and analyzed.